2013
DOI: 10.1371/journal.pgen.1003238
|View full text |Cite
|
Sign up to set email alerts
|

An Incompatibility between a Mitochondrial tRNA and Its Nuclear-Encoded tRNA Synthetase Compromises Development and Fitness in Drosophila

Abstract: Mitochondrial transcription, translation, and respiration require interactions between genes encoded in two distinct genomes, generating the potential for mutations in nuclear and mitochondrial genomes to interact epistatically and cause incompatibilities that decrease fitness. Mitochondrial-nuclear epistasis for fitness has been documented within and between populations and species of diverse taxa, but rarely has the genetic or mechanistic basis of these mitochondrial–nuclear interactions been elucidated, lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
328
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(349 citation statements)
references
References 71 publications
17
328
2
2
Order By: Relevance
“…Similarly, recent hybridization studies in the fruit fly revealed a pronounced mitonuclear incompatibility, which was traced specifically to the mtDNA encoded tRNA TYR of Drosophila simulans and the nuclear-encoded mitochondrial tyrosyl-tRNA synthetase of D. melanogaster [90]. This specific incompatibility decreases the activity of mETS complexes I, II and IV, compromises bristle formation, delays development and decreases fecundity [90]. A similar decline in OXPHOS capacity was previously documented in backcrosses of D. simulans and Drosophila mauritiana [91], and decreased fertility, fecundity and offspring viability, ultimately leading to hybrid breakdown in parasitoid wasps [92][93][94], and extensive mitonuclear epistatic interaction in the fruit fly [95].…”
Section: Interspecies Interactionsmentioning
confidence: 92%
“…Similarly, recent hybridization studies in the fruit fly revealed a pronounced mitonuclear incompatibility, which was traced specifically to the mtDNA encoded tRNA TYR of Drosophila simulans and the nuclear-encoded mitochondrial tyrosyl-tRNA synthetase of D. melanogaster [90]. This specific incompatibility decreases the activity of mETS complexes I, II and IV, compromises bristle formation, delays development and decreases fecundity [90]. A similar decline in OXPHOS capacity was previously documented in backcrosses of D. simulans and Drosophila mauritiana [91], and decreased fertility, fecundity and offspring viability, ultimately leading to hybrid breakdown in parasitoid wasps [92][93][94], and extensive mitonuclear epistatic interaction in the fruit fly [95].…”
Section: Interspecies Interactionsmentioning
confidence: 92%
“…Many different mitochondrial and nuclear genes can be involved in hybrid incompatibilities, including subunits of the ETC and components of transcriptional and translational mechanisms (Burton and Barreto 2012; Meiklejohn et al. 2013; Levin et al. 2014; Hill 2015), but cytochrome c oxidase (complex IV) and cytochrome c are frequently implicated in incompatibilities (Rawson and Burton 2002; Sackton et al.…”
Section: Introductionmentioning
confidence: 99%
“…The first genetic model of speciation, described by Bateson, Dobzhansky and Muller (the BDM incompatibility model, S1 Fig., [22][23][24]), predicts that mutations at two genetic loci differentially accumulating along two lineages can negatively interact in their hybrids. Empirical research has shown that these types of negative epistatic interactions are remarkably common [25][26][27][28][29]; reviewed in [24,30,31].…”
Section: Introductionmentioning
confidence: 99%